Design and fabrication of agriculture pump sprayer trolley / Muhammad Shazril Nazmi Mohd Nizam - Mohd Nizam, Muhammad Shazril Nazmi (2023)
Agriculture sector is very important in our country. Effective method will ease the process to produce a high quality product. The agriculture pump sprayer trolley is used for watering and fertilizing crops. My objective of this project is to design and analysis an Agriculture Pump Sprayer Trolley and to fabricate an affordable and functional Agriculture Pump Sprayer Trolley. The problem that users faced is most of the agriculture pump sprayer nowadays is heavy, hard to operated and not a user friendly. Plus, most of that pump sprayer also take time and energy to be operated because people need to bring it at their back. So, in my project I will try to make an affordable and machine that easy to use. The expected result is to make a functional pump sprayer for the gardener or others. In conclusion, I hope my project will solve the problems that user faced